Evaluation of anxiolytic activity of the essential oil of the aerial part of Foeniculum vulgare Miller in mice - Mesfin, Miraf (BioMed Central, 2014)
BACKGROUND: Foeniculum vulgare locally known as ensilal, is an aromatic plant widely cultivated in temperate and tropical regions. The anti-anxiety activity of the crude extract of F. vulgare has been reported. However, the fraction responsible for anxiolytic activity is not known and there is no any report on the anti-anxiety activity of the essential oil of F. vulgare. The objective of study was to evaluate the anxiolytic activity of the essential oil of Foeniculum vulgare Miller. METHODS: Adult Swiss albino male mice were randomly divided into six groups (n = 6). Groups I and II received Tween 80 (5%, v/v) and diazepam (0.5 mg/kg, ip), respectively, while groups III to V received orally 50, 100, and 200 and 400 mg/kg doses of the essential oil of F. vulgare, respectively. The mice were then individually placed in animal anxiety models: elevated plus maze (EPM), staircase test (SCT) and open field test (OFT) and evaluated for various parameters. RESULTS: In EPM test, 100 and 200 mg/kg doses of the essential oil significantly increased percent number of entries and time spent in open arms compared to control. In SCT these doses also reduced rearing significantly compared to controls, while only the 200 mg/kg dose significantly increased number of squares crossed at the center in the OFT test. CONCLUSION: The essential oil of F. vulgare was found to exhibit a promising anxiolytic activity.